The phenomenon of Ethnic Minorities and the Ottoman State’s policy Towards it (1839-1939 AD) - Riadh Khalil Hussein (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research dealt with an important and vital aspect of the history of the Turkish state in the modern era, where the study focused on a phenomenon of political and humanitarian phenomena in a period that is one of the most prominent periods in its history full of events, facts, turmoil and accumulations, which produced many political entities that were stained with religious and national character, and it was It has the greatest impact on the dismantling of this Ottoman state, its fragmentation, its fall, and the establishment of its ruins. This is the phenomenon of religious and national ethnic minorities in it, which deserves to be carefully studied and studied in order to find out what it is, its nature, objectives, problems, impact and the state’s policy towards it, and since there is no independent academic study that deals with its dispersal. We chose her as a topic for our research. Therefore, this research came entitled (the phenomenon of ethnic minorities and the policy of the Ottoman state towards it 1839-1939 AD), and after collecting the scientific material, we divided the research into three sections, and an introduction and conclusion, we dealt with in the first topic the definition of the research terms, and in the second topic a historical overview of the emergence of minorities Ethnicity and its impact on the Ottoman state, while we devoted the third topic to the Turkish state’s policy towards ethnic minorities (1839-1939 CE), then we deposited the conclusion a summary of the results that came out of the research, and we announced that we have succeeded in drawing a close and accurate picture of this Turkish phenomenon in that period of its history the talk